1992
DOI: 10.1597/1545-1569_1992_029_0032_soomai_2.3.co_2
|View full text |Cite
|
Sign up to set email alerts
|

Superior Orbicularis Oris Muscle Activity in Children with and without Cleft Lip and Palate

Abstract: An analysis of integrated electromyographic (IEMG) activity of the superior orbicularis oris muscle was undertaken in 15 children with cleft lip and palate who have undergone surgery compared to 10 children without clefts (control group). Bipolar surface electrodes were used for IEMG recordings of resting level activity and during the swallowing of saliva. Similar resting level activity was observed in both groups. During the swallowing of saliva, activity in children with cleft lip and palate was higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
0
10
0
7
Order By: Relevance
“…The EMG method is painless and innocuous, and these are important factors when conducting studies involving children. Electromyographic studies of upper lip muscle function have previously been completed on cleft lip and palate subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The EMG method is painless and innocuous, and these are important factors when conducting studies involving children. Electromyographic studies of upper lip muscle function have previously been completed on cleft lip and palate subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In 1992, Carvajal et al reported that children with repaired cleft lip with abnormal lip seal showed higher electromyographic (EMG) activity during the swallowing of saliva. 10 In 2000, Ravera et al added that a significantly higher level of superior orbicularis oris muscle electromyographic activity at rest as well as during swallowing in children with repaired unilateral cleft lip than other normal children. They also suggested a correlation between this hyperactivity and presence of shorter upper lip and abnormal lip seal.…”
Section: Discussionmentioning
confidence: 99%
“…Em estudo realizado com crianças que apresentavam fissura de lábio e palato já operada, Carvajal et al (1992) Em outro estudo, Genaro (1995) avaliou a atividade eletromiográfica do lábio superior associada à medida da pressão intraoral, em 47 adultos com fissura labiopalatina operada, envolvendo fissura labial isolada, fissura palatina isolada e fissura de lábio e palato, além de 24 adultos sem fissura. A emissão da sílaba "pa" e da palavra "rampa" foram utilizadas como tarefas, bem como a emissão da vogal "u" e a protrusão labial.…”
Section: Revisão De Literaturaunclassified
“…Na avaliação da função labial pode ser utilizada a eletromiografia, seja durante a realização de movimentos isolados, como também durante a fala (Farret, Vitti e Farret 1982, Rastatter, DeJarnette 1984a, 1984b, Rasheed e Munshi 1996, Marchiori e Vitti 1996a, 1996b, Schievano, Rontani e Bérzin 1999, Yamaguchi et al 2000, Wholert e Smith 2002, Povh et al 2003, Regalo et al 2005, Felício et al 2007, Ambrosio et al 2009a, 2009b e Afonso 2011). Estudos envolvendo indivíduos com fissura labiopalatina, em geral, encontraram diferença na atividade eletromiográfica do lábio superior ao comparar com indivíduos sem fissura, apesar de utilizarem diferentes métodos de investigação (Spinadel et al 1968, Olscamp, McGuire e Rastater 1986, Göz, Joos e Schilli 1987, Caldeira 1990, Carvajal et al 1992 Lin e Fu 1994, Genaro, Trindade Júnior e Trindade 1994, Carvajal et al 1995, Genaro 1995 , porém este teste tem sido pouco utilizado nos estudos relacionados a indivíduos com fissura labiopalatina (Howard 2004, Kummer et al 2007e Brisso Véliz 2007. Somente um estudo refere-se a parâmetros ligados ao ritmo e intensidade, além da velocidade, porém somente durante a emissão de uma sílaba, encontrando menor intensidade media durante a velocidade no grupo com fissura, justificada pela diminuição da pressão intraoral.…”
Section: Introductionunclassified